Pengembangan LKPD Berbasis Problem Solving pada Tema 8 Subtema 3 Aturan Keselamatan di Perjalanan Kelas II SDN 73 Pontianak Barat - Deviani Deviani; Kartono Kartono; Siti Halidjah (Journal on Education, 2023)
This research aims at problem solving based students worksheets that is valid for use by second grade students of SD Negeri 73 West Pontianak on theme 8 subtheme 3 safety rules on the trip. This type of research is development research by adopting the Borg and Gall model by taking 4 steps out of 10 steps, namely, (1) Potential and problems, (2) Data collection, (3) Product design, (4) Design validation. The data obtained is mixed data, namely quantitative data obtained from the results of the questionnaire assessment of expert validators and practitioners as well as qualitative data that shows the level of validity of the product developed. The research instruments used were interview guidelines and questionnaires. The level of media validity is based on the results of the assessment by 2 material experts and 2 design experts. The assessment results from design experts obtained an average score of 4.75 with very valid criteria and an average score of 4.75 from material experts with very valid criteria